Anti-war and anti-draft student protest - Spartan Daily News:::Creator::::::::::::
Students rally on campus in opposition to the Vietnam War and to the draft. In this view a student is speaking into a megaphone to large crowd of students. A mock oversized poster is partially visible and reads:Selective Service System Certificate; Resist April 29, 1968 written across the certificate.